1978
DOI: 10.1128/aem.36.2.330-340.1978
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Parameters of the Conversion of Methane Precursors to Methane in a Hypereutrophic Lake Sediment

Abstract: The kinetic parameters Ki, V,,,m, Tt (turnover time), and v (natural velocity) were determined for H2 and acetate conversion to methane by Wintergreen Lake sediment, using short-tern (a few hours) methods and incubation temperatures of 10 to 140C. Estimates of the Michaelis-Menten constant, Km, for both the consumption of hydrogen and the conversion of hydrogen to methane by sediment microflora averaged about 0.024 pmol g-' of dry sediment. The maximnal velocity, Vmax, averaged 4.8 ,umol of H2 g h-1 for hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 11 publications
3
30
0
Order By: Relevance
“…Hydrogen concentrations in the sediments we examined ranged from < 5 nM to about 60, with the lowest concentrations found near the sediment-water interface. These concentrations are an order of magnitude lower than those generally found in freshwater sediments (Strayer and Tiedje 1978;Michener 1985;Michener et al submitted) and are one to three orders of magnitude greater than concentrations found in anoxic water columns (Bullister et al 1982;Lilley et al 1982;Scranton et al 1984).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Hydrogen concentrations in the sediments we examined ranged from < 5 nM to about 60, with the lowest concentrations found near the sediment-water interface. These concentrations are an order of magnitude lower than those generally found in freshwater sediments (Strayer and Tiedje 1978;Michener 1985;Michener et al submitted) and are one to three orders of magnitude greater than concentrations found in anoxic water columns (Bullister et al 1982;Lilley et al 1982;Scranton et al 1984).…”
Section: Discussionmentioning
confidence: 60%
“…It seems reasonable to speculate that H2 concentrations in the deep methanogenic sediments of Skan Bay may bc the source of the higher levels of hydrogen at the bottom of the core. Concentrations in freshwater methanogcnic sediments are often quite high (> 150 nM;Strayer and Tiedje 1978;Michener 1985); however, no one has yet measured hydrogen concentrations in methanogenic marine sediments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively high acetate concentrations detected in Wintergreen Lake sediments, however, suggested that acetate was not a limiting factor for methanogenesis in these sediments. Kinetic experiments using (2-'*C) acetate and Wintergreen Lake sediments collected during the summer indicated that the rate of conversion of acetate to methane appeared to be very close to the maximal rate for this reaction in these sediments (Strayer & Tiedje, 1978a). These results suggest that anaerobic metabolism in Wintergreen Lake sediments closely resembles that found in anaerobic sewage digesters where decomposition may be limited by the rate at which methanogenic bacteria utilize acetate (Zeikus.…”
Section: Discussionmentioning
confidence: 84%
“…Many workers have illustrated the importance of acetate as a methane precursor in both frezhwaters and marine sediments [89,99,100], and demonstrated that H2 is a rate limiting factor in the process of methanogenesis in sediments [90,[101][102][103]. Landfills constitute another type of habitat from which methanogens have been isolated [104].…”
Section: [98]mentioning
confidence: 99%